Effect of rhizobia inoculation and seaweed extract (Ecklonia maxima) application on the growth, symbiotic performance and nutritional content of cowpea (Vigna unguiculata (L.) Walp.) - Gyogluu Wardjomto, Cynthia; Mohammed, Mustapha; Ngmenzuma, Titus Y.; Mohale, Keletso C. (Frontiers in Agronomy, 2023)
Research efforts to develop alternatives to chemical-based fertilizers for sustainable crop production has led to renewed interest in beneficial soil microbes such as rhizobia and plant growth promoting biostimulants such as the seaweed (Ecklonia maxima). This study assessed the interactive effect of the co-application of seaweed extract with two Bradyrhizobium strains (Inoculant 1 and Inoculant 2) on the growth, symbiotic performance and nutritional composition of three cowpea (Vigna unguiculata (L.) Walp.) genotypes (IT97K-390-2, Songotra and TVU13998) grown under glasshouse conditions. The response of cowpea to the treatments was genotype dependent, such that the combined application of inoculant 2 plus seaweed extract increased nodule dry matter in genotype Songotra, and together with sole inoculant 2 increased the parameter in genotype IT97K-390-2, just as the inoculation plus seaweed extract treatments increased the parameter in genotype TVU13998 when compared to their respective counterparts receiving other treatments. Sole inoculation or inoculation plus seaweed extract treatments increased shoot dry matter in all varieties (2.0 to 7.2 g.plant-1) relative to the control plants receiving sole nitrate (0.5 to 1.2 g.plant-1), sole seaweed extract (0.3 g.plant-1), nitrate plus seaweed extract (1.2 to 1.6 g.plant-1) or the absolute control (0.2 g.plant-1). Due to N2 fixation in the inoculated plants, their leaf δ15N (-2.66‰ to -1.20‰) were markedly lower (p<0.05) than values recorded by the control plants (+3.30‰ to +510‰) which had no nodules; consequently, leaf N accumulation was greater in the inoculation-based treatments (41.2 to 258.2 mg.plant-1) relative to the uninoculated controls (1.7 to 24.7 mg.plant-1). In most instances, the sole inoculation and inoculation plus seaweed extract treatments increased leaf photosynthetic rates (except for genotype TVU13998 treated with inoculant 1 + seaweed extract), water use efficiency (δ13C) (except in genotype TVU13998) and the concentrations of macro and micronutrients in leaves (except for K in Songotra treated with inoculant 1 or inoculant 1 + seaweed extract as well as Mn in TVU13998 treated with inoculant 1 among others) of the cowpeas relative to the controls. We highlight the potential benefits of the synergistic interactions between rhizobia and seaweed extract for enhancing plant growth and nutrient accumulation in cowpea leaves.